Markets and Policy Measures in the Evolution of Electric Mobility - Fornahl, Dirk.; Hülsmann, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This edited monograph collects theoretical, empirical and political contributions from different fields, focusing on the commercial launch of electric mobility, and intending to shed more light on the complexity of supply and demand. It is an ongoing discussion, both in the public as well as in academia, whether or not electric mobility is capable of gaining a considerable market share in the near future. The target audience primarily comprises researchers and practitioners in the field, but the book may also be beneficial for graduate students.
Introduction -- Strategic perspectives of electric mobility - Steps towards the slope of enlightenment -- On the road to an electric mobility mass market - How can early adopters be characterized? -- How to increase the attractiveness of electric cars as fleet cars? -- Flexible Carsharing - Potential for the Diffusion of Electric Mobility -- Public e-mobility funding and its influence on cooperation and innovation -- China's leapfrog to new electric vehicles.
Keywords: Automotive engineering; Technological innovations; Transportation engineering; Traffic engineering; Automotive Engineering; Innovation and Technology Management; Transportation Technology and Traffic Engineering